Decentralized authentication system utilizing blockchain - Wee, Chun Ming (2022)

(untitled)
This project is a development-based project that specific in cybersecurity area. At present time, the blockchain technology become more popular and be adopted in many types of approach and solution. The reason is blockchain offer the decentralized, integrity, immutable, security enhancement and others benefits that are many people need. At the same time, the traditional database may not secure enough anymore so the blockchain database is appeared to solve the concerns. The blockchain is suitable be used in enhance security that able to against those cyberattacks or the actions that try to damage the data records. Thus, the propose of this project is aim to produce an authentication system utilizing the blockchain database. The database will be used as public ledger but at the same time the confidentiality of the login credentials needs to be provided as well. At the meanwhile, the data integrity also needs to be ensured. Thanks to one of the blockchain unique characteristics which is immutable, this is to prevent data tampered and modification be executed on the blockchain record. ProvenDB is a blockchain database which is MongoDB compatible database service that integrate with blockchain. Thus, precisely to say is the database that been used in this project is MongoDB which is a non-relational document-oriented database; while applied blockchain is public Bitcoin blockchain. In the end, ProvenDB is a technology that combine from these 2 mentioned technologies so this project only deals with 1 instead of 2 sides of technology at the same time. ProvenDB consist of rich and many operations on the MongoDB basis and complement with query that only can applied to blockchain. Moreover, the blockchain will play the role for responsible in store, validate, proof data. Last but not least, the blockchain also can be used to prevent some malicious attack like data tampered, data modifications, ransomware attack, record hacking and others in this project. In conclusion, this project will be utilizing the blockchain technology in order to enhance system security.